Field trials of suction caissons in sand for offshore wind turbine foundations - Houlsby, G; Kelly, R; Huxtable, J; Byrne, B (2006)
A programme of testing on suction caisson foundations in an artificially prepared sand test bed near Luce Bay, in Scotland, is described. The tests are relevant to the design of either monopod or quadruped foundations for offshore wind turbines. Records are presented for suction installation of the caissons, cyclic moment loading under both quasi-static and dynamic conditions to simulate the behaviour of a monopod foundation, and cyclic vertical loading and pullout of caissons to simulate one footing in a quadruped foundation. Variations of stiffness with loading level of the foundation are observed, with high initial stiffness followed by hysteretic behaviour at moderate loads and degradation of response at high loads. Some implications for the design of wind turbine foundations are briefly discussed.